Analysis Determinants of Unwanted Pregnancy in Adolescents : Literature Review - Dwi Ristanti, Adenia; Wijayanti, Wijayanti; Wulandari, Retno (Journal of Advanced Nursing and Health Sciences, 2024)
Background: Pregnancy in teenagers beginning from pregnancy no desired, is one phenomenon recent social. This the more increase occurs in the environment public give rise to its height possible abortion triggering an increase in the MMR Evidence search strategy: this research is a literature review research using the ScienceDirect, PUBMED, BMC, and Google Scholar databases with keywords _ "unwanted pregnancy", "unintended pregnancies in teenagers", and "analysis of unwanted pregnancy". Discussion : Total articles obtained of 20,437 articles, 13 articles were found that met the requirements criteria inclusion with year publications 2020 to 2023, in the form of original articles, articles available in full text form and free access. Causative factor happen non pregnancy desired by teenagers that is exists internal factors and factors external. Impact non pregnancy desired by teenagers that is impact physical, impact economics, and impact environment. Prevention non pregnancy desired by teenagers that is empowerment teenager women, repair gender inequality, respect right basic humans, and reduce poverty. Conclusion: Unwanted pregnancy has a higher risk of occurring in adolescents with the determinants of the role of parents, the role of friends, level of religiosity, access to pornographic media, knowledge, attitudes and sexual behavior.